Wacana mengenai Retorika Komunikasi: Retorika Politik Anies Baswedan - Wulan Yulian Anggini; Febby Pratama Putra (Neolectura, 2022)
The political issued in Indonesia has recently begun to warm due to the residue of the National and Regional Elections. Especially the 2017 DKI Jakarta Regional Head Election which is full of political and religious intrigue. The election of Anies Baswedan as Governor of Jakarta created two opposing groups, namely supporters and critics. Every policy and statement by Anies is always talked about in the mass media and social media. Anies is aware of this so that every statement issued is always wrapped in neat and structured rhetoric. This study aims to determine the rhetoric of Anies Baswedan and the effect on self-image. The method used is descriptive qualitative. The results finding revealed that Anies' control over his speech was extraordinary. Anies is able to position himself according to his interlocutor, this can be seen from every choice of diction to be expressed, technical, intonation, and the way of speaking is never emotional. Rhetoric is very important for a leader as a prerequisite for conveying and persuading audiences, especially in today's modern era where it is easy for audiences to get digital access and it is easy to see the figure of leader.